Role of Generic Competence in Emotional Intelligence and Academic Achievement of University Students - Yasmeen, Rahat; Syeda, Zunaira Fatima; Naseer, Sehrish (JCTE, 2024)
This research aim was to analyze “Role of Generic Competence in Emotional Intelligence and Academic Achievement of University Students”. Quantitative survey research design was used for this research. All students at University of Sargodha, were the population of the study. Convenience sampling technique was used for data collection. 320 students from Faculty of Arts and Humanities (Department of English), Faculty of Social Sciences (Department of Social Work), Faculty of Medical and Health Sciences (Sargodha Medical College) and Faculty of Agriculture (Department of Plant Pathology) were selected conveniently. Two adopted instruments were used in study. The online Google form was used for data collection. Mediation analysis techniques were used to assess the Role of Generic Competence in Emotional Intelligence and Academic Achievement of University Students. The findings of the study produced an insignificant mediating role of Generic Competence in Emotional Intelligence and Academic Achievement of University Students. It is recommended that universities need to provide guideline to curriculum developers to design such curriculum and evaluation system to fulfill the emerging needs of students and professionals.